Informal STEM learning: Examples from everyday spatial behaviors - Yang, Yingying; Conde Santiago, Sonia; Lasc, Daria; Hershkovich, Arielle; Grove, Lauren (Frontiers in Psychology, 2023)
Extensive research has shown a close relationship between spatial abilities and success in STEM disciplines because many STEM problems often require students to reason about spatial information. Studying everyday spatial behaviors helps to understand children’s daily experience with STEM-related activities, which may provide insights for informal STEM learning. Therefore, the current study examined children’s everyday spatial behaviors and their associations with broader child development outcomes and individual differences. We developed an everyday spatial behaviors questionnaire for children (ESBQC). A total of 174 parents and their children aged 4-9 years old participated. In EBSQC, parents rated how much difficulty their children experience with different spatial behaviors, such as putting together a puzzle, retracing a route, or hitting a moving ball. Parents rated certain spatial behaviors, such as drawing, navigation, and sports-related activities, as more difficult for their children than other spatial behaviors, such as spatial perception, spatial visualization, and body awareness. ESBQC was positively correlated with age but not with sex. Furthermore, ESBQC was significantly correlated with parent reports of sense of direction, adaptive living skills, and children’s cognitive ability. Our study demonstrated the significance of everyday spatial behaviors as they relate to broader child development outcomes. Our questionnaire may also provide a useful tool for parents and other stakeholders to better understand everyday spatial behaviors and encourage interest and competence in spatial skills, ultimately promoting STEM learning in informal, everyday settings.